2005
DOI: 10.1086/498218
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Clearance of Hepatitis C Virus Nonstructural 3/4A–Expressing Hepatocytes by DNA Vaccine–Primed Cytotoxic T Lymphocytes

Abstract: A key question in the development of a therapeutic vaccine against hepatitis C virus (HCV) is whether vaccine-primed T cells enter the liver and eliminate HCV-expressing hepatocytes. In the absence of an infectious small-animal model, we evaluated liver homing of vaccine-primed T cells in mice with transient hepatic transgene expression of the HCV nonstructural 3/4A (NS3/4A) protein. We found that T cells primed by transdermal DNA-based vaccination entered the liver and cleared NS3/4A-expressing hepatocytes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 16 publications
1
52
0
Order By: Relevance
“…Cells were transfected using 4 mg plasmid DNA together with 6 ml TurboFect in vitro transfection reagent (Fermentas International, Burlington, ON, Canada) and incubated for 36 h before harvesting for analysis of NS3 and HBcAg protein content by immunoprecipitation and Western blot as described (30,34). In brief, cell lysates were applied to protein A-Sepharose beads conjugated with anti-NS3 or anti-HBcAg Abs for 2 h (+4˚C).…”
Section: Transient Transfection and Detection Of Expressed Ns3/4a Andmentioning
confidence: 99%
“…Cells were transfected using 4 mg plasmid DNA together with 6 ml TurboFect in vitro transfection reagent (Fermentas International, Burlington, ON, Canada) and incubated for 36 h before harvesting for analysis of NS3 and HBcAg protein content by immunoprecipitation and Western blot as described (30,34). In brief, cell lysates were applied to protein A-Sepharose beads conjugated with anti-NS3 or anti-HBcAg Abs for 2 h (+4˚C).…”
Section: Transient Transfection and Detection Of Expressed Ns3/4a Andmentioning
confidence: 99%
“…Histochemistry and Immunohistochemistry-Sections and staining of the paraffin or cryosections was performed as described recently (18,23,24). For detection of NS5A, a rabbitderived V5-epitope-specific serum (Invitrogen) was used.…”
Section: Infection Of Mice and Virusmentioning
confidence: 99%
“…While other studies have shown that liver transfection with HCV antigens can be used to assess the cytoxicity of the DNA vaccine induced CD8 + T cell responses in mice 19 and HCV DNA immunization studies in chimpanzees have demonstrated the presence of HCV-specific IFNγ + T cells within the liver, 21 our study is the first to suggest that the liver actively recruits certain subsets of vaccine-specific T cells following peripheral immunization. Additionally, we have shown that the liver recruits vaccine-specific T cells despite the absence of cognate antigen and that this recruitment leads to the formation of a fully functional pool of vaccine-specific T cells able to both clear HCV protein expressing hepatocytes and to upregulate expression of CCR5 and IFNγ within the liver.…”
Section: Discussionmentioning
confidence: 57%
“…[18][19][20] In order to induce liver expression of HCV NS3, C57BL/6 mice were tail vein injected with pConNS3/NS4A using a previously described method of liver transfection. 19 Both naïve and immunized animals received tail vein injections of 100 μg of pConNS3/NS4A and were sacrificed 48 h following injection (Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%